Formation of a competitive status of currency under global integration conditions - Шемет, Тетяна Станіславівна (Technology audit and production reserves, 2014)
This paper presents a theoretical analysis of forming a single global currency status in the context of currency competition. In the author’s opinion, the relevance of researches in this field is justified by intensifying not only regional but also global integration processes, which requires the scientific substantiation of the ways of forming a single currency as a key instrument of global monetary integration. It was concluded that the transitional period of the currency consolidation, which occurs due to the regional integration processes and leads to defining several currency leaders, should be considered as a necessary prerequisite for emerging a single global currency. The specifics of implementing the strategy of the yuan internationalization and the rapid economic growth of the Chinese economy increases the yuan rate in the competition of currency leaders. The competition between the U.S. dollar, the euro and the Chinese yuan as global monetary potential leaders is the engine of forming a single global currency.